Levantamento da ocorrência do raquitismo-da-soqueira em cana-de-açúcar causada por Leifsonia xyli subsp. xyli no noroeste do Paraná - Marcuz, Fernanda Santos (2007)
Ratoon stunting disease is one of the most important worldwide diseases of sugarcane since its first report in Australia in 1950. In the last few years there is an increment in the sugarcane production in the state of Paraná, and surveys regarding the pathogen incidence in this crop are extremely important for controlling measures to increase the production. In this work a survey was conducted in two sugarcane production areas of two sugarcane processing plants in the northwest region of Paraná. To detect the incidence of the bacterium Leifsonia xyli subsp. xyli the method of diagnosis used was the serological detection of the pathogen on xylem extracts by Dot Blot assay with the specific polyclonal antiserum against the bacterium. A total of 1395 samples were collected in 32 production areas cultivated with 10 sugarcane varieties, obtained from plants with different harvest time. The bacterium was detected in the area cultivated with the variety SP77-5181 in a 23% rate of incidence, and PCR assays also confirmed the bacterium incidence in this variety, with specific primers for Leifsonia xyli subsp. xyli. These results are an indication of the incidence of the bacterium in the northwest region of Paraná, despite of apparently not being widely disseminated.